The Role of Law in Promoting Sustainable Finance and Green Investments in Emerging Markets - Fatima Malik; Sara Hussain; Li Wei; Muh. Cendekiawan Ainul Haq (Yayasan Adra Karima Hubbi, 2026)
Background. Growing environmental challenges, climate-related financial risks, and increasing global commitments to sustainable development have intensified the importance of legal frameworks in directing capital toward environmentally responsible investments. Emerging markets face particular pressure to balance rapid economic growth with environmental sustainability while strengthening investor confidence, regulatory transparency, and institutional accountability. Purpose. This study aimed to evaluate the role of law in promoting sustainable finance and green investments in emerging markets by examining the relationships among legal quality, regulatory effectiveness, institutional governance, investor protection, and sustainable financial development. Method. A mixed-methods sequential explanatory design was employed using comparative data from 24 emerging market economies observed over a ten-year period. Quantitative analyses incorporated descriptive statistics, structural equation modeling, hierarchical regression, mediation and moderation analyses, while qualitative evidence from expert interviews, policy document reviews, and institutional observations was analyzed through thematic analysis. Results. Findings demonstrated that legal certainty significantly strengthened sustainable finance development, investor confidence, financial transparency, and green investment performance. Sustainable finance partially mediated the relationship between legal quality and investment outcomes, whereas institutional governance enhanced the effectiveness of regulatory implementation. Conclusion. Sustainable green investment depends upon the coordinated integration of legal certainty, regulatory quality, institutional governance, financial transparency, and environmental accountability, providing an evidence-based foundation for resilient financial systems and long-term sustainable economic development in emerging markets.